Will ‘Yellow’ Unions Disappear After the Amendment to Act on Trade Unions? - Rycak, Magdalena (Acta Universitatis Lodziensis. Folia Iuridica, 2021)
The article aims to answer the question whether, after the amendment to the provisions of Act on trade unions, which entered into force on 1 January 2019, the phenomenon of creating and practical functioning of the so-called ‘yellow’ unions that, although developed as a workers’ organisation but in fact function mainly for the purpose of protecting an employer’s interests, will disappear. The article explains the concept of ‘yellow’ unions, discusses the most important recent amendments to the provisions of Act on trade unions, and analyses the binding provisions with regard to potential ‘profitability’ of the development of yellow unions from the point of view of employers’ interests.